Efficiency and stability of hydrogen production from seawater using solid oxide electrolysis cells. (15th October 2021) - Liu, Zhao; Han, Beibei; Lu, Zhiyi; Guan, Wanbing; Li, Yuanyuan; Song, Changjiang; Chen, Liang; Singhal, Subhash C.
Highlights: Seawater without any treatment was directly used for hydrogen production. High energy conversion efficiency and long-term stability were obtained. The cell did not show any obvious change after operation for 400 h. Abstract: Hydrogen production from seawater electrolysis provides a basis for clean and sustainable development of our energy system. However, in the existing seawater splitting techniques, it is difficult to overcome the damage to electrolyzers by the sea salt. In this work, solid oxide electrolysis was used to split untreated seawater, and its electrochemical performance and long-term stability were studied. The electrolysis was carried out at constant current density of 200 mA/cm −2 for 420 hrs with 183 mL/min hydrogen production and a degradation rate of 4.0%. Energy conversion efficiency of 72.47% was obtained even without reusing the high temperature exhaust gas. After 420 hrs of experiment, it was found that the structure and composition of the cell remained unchanged, showed that long-term operation had no obvious effect on the cell itself. This work shows that the performances of solid oxide electrolysis cell in seawater splitting are excellent, and provides a good choice for energy storage and hydrogen production from seawater.